Analisis Perbandingan Pengaruh Endorser terhadap Sikap pada Merek Shampo Sunsilk dan Shampo Pantene - Rosi, Fatchur; Andjarwati, Anik Lestari (BISMA (Bisnis dan Manajemen), 2018)
Two big player that PT. Unilever Indonesia Tbk with the mainstay Sunsilk product and PT. Procter & Gamble that sells Pantene product stringent to supply the indonesian needs of shampoo. One of that with appearing of endorser in advertising to influence positif attitude of consumer to shampoo brand. This study used to analyzed the comparing endorser effect influence towards brand attitude (attitude toward brand) shampoo Sunsilk and shampoo Pantene in university student of Management of Economic Faculty of State University of Surabaya with 19-24 years old and 62 respondent for shampoo Sunsilk brand and 62 respondent for shampoo Pantene brand. Data were analyzed with simple linear regression.The result of research show, there are positif endorser effect toward brand attitude in both of shampoo brand whereas endorser effect toward brand attitude shampoo Sunsilk higher than endorser effect toward brand attitude shampoo Pantene